Towards Energy Efficient Design of Multi-Radio Platforms for Wireless Sensor Networks - Goraczko, Michel; Lymberopoulos, Dimitrios; Priyantha, Nissanka B.; Zhao, Feng; Priyantha, Bodhi (International Conference on Information Processing in Sensor Networks (IPSN '08), 2008)
We study the problem of concurrently supporting multiple radios with different capabilities and interfaces on a single sensor node platform. Through a detailed experimental study on hardware multi-radio platforms, using the two representative radio technologies 802.15.4 and 802.11, we identify bottlenecks and design tradeoffs that are usually overlooked and that, as we show, have a significant impact on the sensor network"s performance and energy efficiency. Our findings are threefold. We show that a proper pairing of processor and radio is crucial for taking the full advan-tage of the energy efficiency of higher bandwidth radios. The processor/radio pairing affects the energy balance of a sensor node, thus making the design of dynamic switch-ing among multiple radios more challenging. Second, we demonstrate and quantify the impact of network traffic on energy consumption of a sensor node while varying net-work parameters, and illustrate the deficiency of existing energy-optimizing protocols. Our results in